Sistem Pakar Pendiagnosa Infeksi Saluran Pernafasan Akut (ISPA) dengan Metode Forward Chaining dan Certainty Factor - Samuel Njoo; Kartika Gunadi; Henry Novianus Palit (Jurnal Infra, 2021)
Acute Respiratory Infection (ARI) is a group of diseases that are quite common in developing countries, including Indonesia. ARI consists of various diseases and has a very varied possibility of symptoms. If not detected and treated immediately, ARI can get even worse and can lead to death. With an expert system, users can quickly self-diagnose without worrying about the cost or time required. The knowledge possessed by the expert system also comes from doctors in their fields.The expert system will be built with the help of 2 (two) methods, namely the forward chaining as an inference method and the certainty factor as the calculation method. With the forward chaining method, the system can provide information such as what disease the user is suffering from directly after the user fills all the questions that will be asked by the system. In addition, with the certainty factor method, the system can provide information like how sure the system in providing diagnostic results and is intended in the form of a percentage, the user is also presented with several answer choices so each user's answer choices will have an impact on the final diagnosis result by the expert system.The system will be tested by 3 related experts and the accuracy of system diagnosis is 75%.